2011
DOI: 10.1080/01446193.2010.549138
|View full text |Cite
|
Sign up to set email alerts
|

Analyses and evaluation of irregularities in public procurement in India

Abstract: Public procurement is prone to corruption, which in the global construction market alone accounts for an estimated US$340 billion per year. There is a growing need for procurement systems to be able to fight corruption and improve the effectiveness, efficiency, fairness and transparency of public procurement. A comprehensive list of irregularities in public procurement is derived from irregularities observed during technical vigilance inspections by experts and reported cases. The research involved a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 14 publications
2
69
0
2
Order By: Relevance
“…Many researchers utilized Delphi to evaluate the effectiveness of safety programs or systems (Hallowell and Gambatese 2009a;2010a;Rajendran and Gambatese 2009;Hallowell and Calhoun 2011;Hallowell et al 2011;Hon et al 2012;Shapira and Lyachin 2009). Delphi was also used to identify and evaluate personal issues, such as irregular behaviour (Tabish andJha 2011), professional attributes (Hackett andHicks 2007), and engineer competences (Yik et al 2012).…”
Section: Topic Coverage Of the Delphi Papersmentioning
confidence: 99%
“…Many researchers utilized Delphi to evaluate the effectiveness of safety programs or systems (Hallowell and Gambatese 2009a;2010a;Rajendran and Gambatese 2009;Hallowell and Calhoun 2011;Hallowell et al 2011;Hon et al 2012;Shapira and Lyachin 2009). Delphi was also used to identify and evaluate personal issues, such as irregular behaviour (Tabish andJha 2011), professional attributes (Hackett andHicks 2007), and engineer competences (Yik et al 2012).…”
Section: Topic Coverage Of the Delphi Papersmentioning
confidence: 99%
“…Sohail and Cavill (2008) outlined various corruption vulnerabilities and related stakeholders in the project execution and delivery process. Tabish and Jha (2011) further conceived key corruption vulnerabilities in public procurement in terms of irregularities. In their study, Tabish and Jha (2011) identified 61 irregularities in the Indian public procurement projects, and categorized these irregularities into five groups, namely transparency, professional standards, fairness, contract monitoring and regulation, and procedural accountability irregularities.…”
Section: Corruption Vulnerabilitiesmentioning
confidence: 99%
“…In order to overcome limitations of the traditional criteria, academic researchers suggest a variety of criteria for project performance evaluations. Some examples are safety of the project site [66][67][68], geographic location of projects [69], environmental impacts [70] and satisfaction of community, client or customer [71,72]. Moreover, the quality and variety of materials and goods used in a project [73,74], number of active labor force and salaries [75][76][77] and experience and scientific levels of employees in the project [78,79] are amongst other effective measures of project performance.…”
Section: Literature Reviewmentioning
confidence: 99%